Early Children’s Education in Psychological Perspectives and Islamic Values - Siti Nurhidayatul Hasanah (Tarbiyah Departement collaboration with AMCA, 2019)
Get bearing with preeminent generation preparation, early age child education hold position that momentously, between position that held by other scope. It was caused by experience early education gets to give influence that melandasi processes education and succeeding child developing. On childs early age experience psikis's physical and developing growth, namely formative motorik, bicara, emotion, social, creativity, moral, sexual, and personality. In consequence teaching on Early Age Child Education is attributed for moral construction, religion, discipline, lingual ability, energy thoughts, energy composes, emotion, societal ability, and earthly concern skill. In the meantime of Islami's point perspective educations on early age child is emphasized on believe construction, religious service, behavior, intellectual, bodily, psikis, social, and sexual manner.